Yield stress measurement of gelled waxy crude oil: Gap size requirement - Japper-Jaafar, A. (Elsevier, 2015)
The strength of gelled waxy crude oil is an important parameter required to determine the restart pressure of pipelines filled with the gelled waxy crude oil. Several measurement methods have been proposed in the literature to quantify the yield strength utilizing a rheometer. Minimal discussions, are however, provided on the effects of rheometer geometry gap on the yield stress measurements. This study is intended to propose a systematic protocol to determine the geometry gap settings for better repeatability of the yield stress measurements of gelled waxy crude oils. The reliability of the yield stress data measured has been shown to be highly dependent on the gap selection in the rheometer. The ten-to-one gap ratio has been proven to be inapplicable for the case of gelled waxy crude oils which consists of wax crystal networks entrapping the oil phase. Presence and strong interactions of large wax crystals presents wall effects and subsequently reduces the repeatability of the measurements. The method proposed in this study has been proven to work on a mild waxy crude oil as well as on a more "severe" waxy crude oil. It can be utilized prior to any transient rheological measurements as gap setting is crucial to ensure accurate and reliable measurements. Â© 2015 Elsevier B.V.